Knowledge, attitude and practices of breast feeding among post natal mothers - D.C., Divyarani; R. Patil, Goudappa (International Journal of Contemporary Pediatrics, 2017)
Background: Breast feeding is an unequalled way of providing ideal food for the healthy growth and development of infants. The major causes for the mortality and morbidity among infants are malnutrition, diarrhoea, infections, lack of awareness and misconception among mothers regarding breast feeding. This study was conducted to assess the knowledge, attitude and practice of mothers regarding breast feeding. Methods: The study population consisted of mothers in postnatal ward and mothers having a child of less than two years in immunization clinic. The sample size was 600 and technique adopted was Non probability purposive sampling technique. Ethical clearance was obtained and permission from respective authorities was also taken. The instrument used is a predesigned and pretested semi structured questionnaire. Results: Majority of mothers had inadequate knowledge and attitude towards breast feeding. . Age, education, occupation, economic status, religion and type of family were found to be significant associates of their knowledge & attitude. Conclusions: Among many mothers, correct Breast feeding practices were not practiced.